STRATEGI RUMAH MAKAN NASI PADANG SALERO BUNDO DALAM MENJAGA KETAHANAN EKONOMI DI ERA DIGITAL - Ferza Rif’at Elfran Diaryo; Elsya Aulia Putri; Elviana Kholisatun Nisa; Khurotul Aini; Safina Resty Ariyani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The rapid growth of digital technology and economic uncertainty create challenges for Micro, Small, and Medium Enterprises (MSMEs), especially in the culinary sector. Rising food prices, stronger competition, and changing consumer behavior require businesses to adapt. This study examines the strategies used by Salero Bundo Padang Rice Restaurant to maintain economic resilience in the digital era. A qualitative method was applied through observation, interviews, and documentation. The findings show that the restaurant maintains food quality, provides good service, keeps the premises clean, uses digital platforms such as GoFood and ShopeeFood, and adjusts prices when raw material costs increase. The business also creates local jobs and supports the local economy. These strategies strengthen the restaurant's economic resilience.